Regularly patterned multi-section GaN nanorod arrays grown with a pulsed growth technique. (2nd December 2015) - Tu, Charng-Gan; Su, Chia-Ying; Liao, Che-Hao; Hsieh, Chieh; Yao, Yu-Feng; Chen, Hao-Tsung; Lin, Chun-Han; Weng, Chi-Ming; Kiang, Yean-Woei; Yang, C C
Abstract: The growth of regularly patterned multi-section GaN nanorod (NR) arrays based on a pulsed growth technique with metalorganic chemical vapor deposition is demonstrated. Such an NR with multiple sections of different cross-sectional sizes is formed by tapering a uniform cross section to another through stepwise decreasing of the Ga supply duration to reduce the size of the catalytic Ga droplet. Contrast line structures are observed in either a scanning electron microscopy or transmission electron microscopy image of an NR. Such a contrast line-marker corresponds to a thin Ga-rich layer formed at the beginning of GaN precipitation of a pulsed growth cycle and illustrates the boundary between two successive growth cycles in pulsed growth. By analyzing the geometry variation of the contrast line-markers, the morphology evolution in the growth of a multi-section NR, including a tapering process, can be traced. Such a morphology variation is controlled by the size of the catalytic Ga droplet and its coverage range on the slant facets at the top of an NR. The comparison of emission spectra between single-, two-, and three-section GaN NRs with sidewall InGaN/GaN quantum wells indicates that a multi-section NR can lead to a significantly broader sidewall emission spectrum.